Does Chondrocalcinosis Associate With a Distinct Radiographic Phenotype of Osteoarthritis in Knees and Hips? A Case–Control Study. Issue 2 (February 2016) - Abhishek, A.; Doherty, S.; Maciewicz, R. A.; Muir, K.; Zhang, W.; Doherty, M.
Abstract : Objective: To examine if knee chondrocalcinosis (CC), hip CC, or CC at distant joints associates with a distinct radiographic phenotype of osteoarthritis (OA) in knees or hips. Methods: We conducted a case–control study using data from the Genetics of Osteoarthritis and Lifestyle (GOAL) study (n = 3, 170). All participants of the GOAL study had radiographs of knees, hands, and pelvis, which have been scored for CC and for individual radiographic features of OA. For this study, cases had radiographic OA and CC, and controls had radiographic OA without CC at the index joint. Data for knees and hips were analyzed separately. Binary logistic regression was used to examine the association between each radiographic phenotype and CC in joints with OA. Generalized estimating equation analysis was used to account for correlated data. Results: Knee CC, and CC at any distant joint (without knee CC), associated with attrition in knee OA (adjusted odds ratio 2.32 [95% confidence interval 1.42–3.79] and 2.42 [1.41–4.13], respectively). There was no association between knee CC and osteophytosis or joint space narrowing (JSN) in knees with OA. Hip CC associated negatively with the summated osteophyte score and minimum JSN in hip OA. However, in hips with OA, CC did not associate with cysts or sclerosis. Additionally, distant joint CC did not associate with any structural change in hip OA. Conclusion: This study demonstrates that knee CC and CC at distant joints associate with attrition in knee OA, and hip CC associates with a milder hip OA phenotype. There was no evidence that CC associates with a hypertrophic OA phenotype.